2019
DOI: 10.2196/13728
|View full text |Cite
|
Sign up to set email alerts
|

A Behavioral Activation Mobile Health App for Smokers With Depression: Development and Pilot Evaluation in a Single-Arm Trial

Abstract: BackgroundThe integration of Behavioral Activation Treatment for Depression (BAT-D) into smoking cessation interventions is a promising approach to address depression as a barrier to quitting. However, this approach has only been tested as a face-to-face intervention, which has low reach.ObjectiveThe aims of the study were to develop a BAT-D mobile health app with high potential reach and determine its feasibility, acceptability, and preliminary effects on theory-based behavioral processes of behavioral activa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Heffner et al (2019) evaluated Actify! , a mobile health application, for its effects on depression, cigarette abstinence, and engagement with the program among smokers with depression.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Heffner et al (2019) evaluated Actify! , a mobile health application, for its effects on depression, cigarette abstinence, and engagement with the program among smokers with depression.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, some studies reported on non-BA comparison interventions which were similarly effective to BA (e.g., Ledari et al, 2018; Martinez-Vispo et al, 2019) or more effective than BA (e.g., Eisma et al, 2015) at reducing depression. In addition, the external validity of some of the included studies is questionable for reasons such as enrollment of female participants (Kern et al, 2019; Schneider et al, 2016; Thomas & Al-Anouti, 2018) or Veterans (Naik et al, 2019) alone, lack of a control condition (Heffner et al, 2019; Hellerstein et al, 2015; Ledari et al, 2018; Magidson et al, 2014; Solomonov et al, 2019; Tull et al, 2018), or inadequate sample size (Ledari et al, 2018; Magidson et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are countless mobile applications that aim to influence the population's health (mHealth). These applications are designed to address different issues, such as blood pressure monitoring (Wang et al, 2019), stress management (Hwang & Jo, 2019), smoking cessation counseling (Heffner et al, 2019), or weight management (Cueto et al, 2019). For maternal and neonatal care, there are also applications (Sondaal et al, 2016), focusing on child care, pregnancy, and before pregnancy (Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%